2010
DOI: 10.1016/j.bpj.2009.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Concentration Dependence of Viral Capsid Assembly Kinetics—the Origin of the Lag Time and Identifying the Critical Nucleus Size

Abstract: The kinetics for the assembly of viral proteins into a population of capsids can be measured in vitro with size exclusion chromatography or dynamic light scattering, but extracting mechanistic information from these studies is challenging. For example, it is not straightforward to determine the critical nucleus size or the elongation time (the time required for a nucleus to grow to completion). In this work, we study theoretical and computational models for capsid assembly to show that the critical nucleus siz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
191
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(201 citation statements)
references
References 47 publications
9
191
0
1
Order By: Relevance
“…3 and 4). In the patchy sphere model, assembly for the weakest subunitnanoparticle interaction (ε S = 6.6) is heavily nucleationdominated, while for the strongest value (ε S = 9) the nucleation timescale is comparable to the elongation timescale 128 (i.e., the time required for a critical nucleus to grow to completion 129 ). These two scenarios are distinguished by the spectrum of implied timescales (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3 and 4). In the patchy sphere model, assembly for the weakest subunitnanoparticle interaction (ε S = 6.6) is heavily nucleationdominated, while for the strongest value (ε S = 9) the nucleation timescale is comparable to the elongation timescale 128 (i.e., the time required for a critical nucleus to grow to completion 129 ). These two scenarios are distinguished by the spectrum of implied timescales (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, while the CPU time for unbiased dynamics increases with decreasing total subunit concentration c 0 according to ∼ c n * 0 with n* the critical nucleus size, the MSM approach will scale as the minimum assembly time,∼ c −1 0 (Ref. 129). This scaling could be further improved upon using coordinates that consider positions of free subunits (e.g., w described in Sec.…”
Section: B Expected Scaling Of the Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the infected cell, the K250/2D Cp and the K2502/E Cp may become kinetically trapped by this interaction, unable to continue down the NC assembly pathway. Computational studies with other RNA viruses have demonstrated, counterintuitively, that increasing the affinity of a viral Cp for its cognate RNA leads to an aberrant and incorrect NC assembly pathway by altering the rate of nucleation (8,21).…”
Section: Fig 8 Em Analysis Of Cells Infected With Double Cde2/capsid mentioning
confidence: 99%